2013
DOI: 10.1016/j.ydbio.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Mummy, A UDP-N-acetylglucosamine pyrophosphorylase, modulates DPP signaling in the embryonic epidermis of Drosophila

Abstract: The evolutionarily conserved JNK/AP-1 (Jun N-terminal kinase/activator protein 1) and BMP (Bone Morphogenetic Protein) signaling cascades are deployed hierarchically to regulate dorsal closure in the fruit fly Drosophila melanogaster. In this developmental context, the JNK/AP-1 signaling cascade transcriptionally activates BMP signaling in leading edge epidermal cells. Here we show that the mummy (mmy) gene product, which is required for dorsal closure, functions as a BMP signaling antagonist. Genetic and bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 49 publications
1
39
0
Order By: Relevance
“…Dpp signaling expansion in sxc mutants is identical to that which we documented previously in mmy 1 mutants (Humphreys et al, 2013). In this regard, we observed that while pMad immunoreactivity extends to a maximum average depth of five cells in the epidermis of wild-type embryos, immunoreactivity extends to a maximum average depth of ten cells in similarly staged sxc mutants ( Figure 3G).…”
Section: Sxc Antagonizes Dpp/bmp Signalingsupporting
confidence: 87%
See 4 more Smart Citations
“…Dpp signaling expansion in sxc mutants is identical to that which we documented previously in mmy 1 mutants (Humphreys et al, 2013). In this regard, we observed that while pMad immunoreactivity extends to a maximum average depth of five cells in the epidermis of wild-type embryos, immunoreactivity extends to a maximum average depth of ten cells in similarly staged sxc mutants ( Figure 3G).…”
Section: Sxc Antagonizes Dpp/bmp Signalingsupporting
confidence: 87%
“…The sxc-encoded OGT is required for embryonic development mmy codes for the single UDP-N-acetylglucosamine pyrophosphorylase in Drosophila (Schimmelpfeng et al, 2006), and its requirement for attenuating epidermal BMP signaling during dorsal closure points to a previously unrecognized role for glycosylation in defining a restricted BMP activity field in the fly (Humphreys et al, 2013). UDP-GlcNAc serves as the precursor for a diverse set of glycosyl modifications that are catalyzed by a similarly diverse set of transferase enzymes (Lairson et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations